2013
DOI: 10.1105/tpc.112.107896
|View full text |Cite
|
Sign up to set email alerts
|

CYCLIN-DEPENDENT KINASE G1 Is Associated with the Spliceosome to RegulateCALLOSE SYNTHASE5Splicing and Pollen Wall Formation inArabidopsis     

Abstract: Arabidopsis thaliana CYCLIN-DEPEDENT KINASE G1 (CDKG1) belongs to the family of cyclin-dependent protein kinases that were originally characterized as cell cycle regulators in eukaryotes. Here, we report that CDKG1 regulates pre-mRNA splicing of CALLOSE SYNTHASE5 (CalS5) and, therefore, pollen wall formation. The knockout mutant cdkg1 exhibits reduced male fertility with impaired callose synthesis and abnormal pollen wall formation. The sixth intron in CalS5 pre-mRNA, a rare type of intron with a GC 59 splice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 61 publications
3
62
0
9
Order By: Relevance
“…The large isoform of CDK11 (the mammalian homolog) promotes pre-mRNA splicing through its interaction with CyclinL (33), and a similar function has been proposed for CyclinL in plants (21), where it is required for the correct splicing of disease resistance transcripts. Indeed, CDKG1 was found to be associated with the spliceosome and regulates the splicing of a gene involved in pollen cell wall formation (34), indicating a general role in regulating several different aspects of pollen development.…”
Section: Discussionmentioning
confidence: 99%
“…The large isoform of CDK11 (the mammalian homolog) promotes pre-mRNA splicing through its interaction with CyclinL (33), and a similar function has been proposed for CyclinL in plants (21), where it is required for the correct splicing of disease resistance transcripts. Indeed, CDKG1 was found to be associated with the spliceosome and regulates the splicing of a gene involved in pollen cell wall formation (34), indicating a general role in regulating several different aspects of pollen development.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these results show that ARF17 directly regulates CalS5 expression in callose synthesis. Recently, Huang et al (2013) showed that CDKG1 can interact with the splicing factor to regulate CalS5 splicing and pollen wall formation. In addition, CalS5 expression is also decreased in rpg1 and npu mutants (Chang et al, 2012;Sun et al, 2013), indicating that CalS5 expression is regulated at multiple levels.…”
Section: Discussionmentioning
confidence: 99%
“…CALLOSE SYNTHASE5 (CalS5) is the major enzyme responsible for the biosynthesis of the callose peripheral of the tetrad (Dong et al, 2005;Nishikawa et al, 2005). Mutation of Cals5 and abnormal CalS5 pre-mRNA splicing resulted in defective peripheral callose deposition and primexine formation (Dong et al, 2005;Nishikawa et al, 2005;Huang et al, 2013). Besides CalS5, four membrane-associated proteins have also been reported to be involved in primexine formation: DEFECTIVE EXINE FORMATION1 (DEX1; Paxson-Sowders et al, 1997, 2001, NO EXINE FOR-MATION1 (NEF1; Ariizumi et al, 2004), RUPTURED POLLEN GRAIN1 (RPG1; Guan et al, 2008;Sun et al, 2013), and NO PRIMEXINE AND PLASMA MEM-BRANE UNDULATION (NPU; Chang et al, 2012).…”
mentioning
confidence: 99%
“…A knockout mutant of CDKG1 exhibited a low panicle seed setting rate, and further work indicated that the sixth intron of the CDKG1 pre-mRNA was altered in the cdkg1 mutant. 47 Consistent with mammalian CRK7, a GFP-CDKG1 fusion protein was found to co-localize with spliceosomal components, and it was proposed to couple splicing with transcription (a cyclin-dependent protein kinase, CDKC2, colocalizes with and modulates the distribution of spliceosomal components in Arabidopsis). The regulation of GSLs in higher plants includes both transcriptional and post-translational modifications such as phosphorylation and direct translocation.…”
Section: Callose Biosynthesis During Male Reproductive Development Inmentioning
confidence: 80%